Inflation targeting and monetary policy rules - Patalinghug, Jason C. (Global Economic Observer, 2018)
This paper examines the literature to try to explain the concept of inflation targeting. There are at present two competing monetary policy rules: (1) targeting rules and (2) instrument rules. The objective of this paper is to review the relative merits of these two monetary policy rules. The debate between using either an inflation targeting rule or an instrument rule debate displays the lack of consensus among economists concerning the proper specification and underlying assumptions of the inflation-targeting model which is suited for the analysis of key monetary policy issues. The paper also examines what recent studies have found about the effect of inflation targeting on emerging markets. These studies have shown that inflation targeting has been largely beneficial to emerging markets.
Keywords: Central Bank; Instrument Rules; Macroeconomics; dept.eco; peer-reviewed; ⛔ No DOI found